2022
DOI: 10.1098/rspb.2022.0399
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiles of consistent risk-taking behaviour across time and contexts in European sea bass

Abstract: Bolder individuals have greater access to food sources and reproductive partners but are also at increased risk of predation. Boldness is believed to be consistent across time and contexts, but few studies have investigated the stability of this trait across variable environments, such as varying stress loads or long periods of time. Moreover, the underlying molecular components of boldness are poorly studied. Here, we report that boldness of 1154 European sea bass, evaluated using group risk-taking tests, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 72 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…The study of the methylome and the transcriptome of the two different behavior types could hold interesting results for aquaculture purposes. These could be further explored in future studies since recent evidence showed differences in transcriptomic analyses between Bold and Shy copying styles for this species (Sadoul et al, 2022). However, a behavior assays study using the olive flounder (Paralichthys olivaceus) only found 144 DEGs out of the entire transcriptome when comparing Bold vs.…”
Section: Tablementioning
confidence: 99%
“…The study of the methylome and the transcriptome of the two different behavior types could hold interesting results for aquaculture purposes. These could be further explored in future studies since recent evidence showed differences in transcriptomic analyses between Bold and Shy copying styles for this species (Sadoul et al, 2022). However, a behavior assays study using the olive flounder (Paralichthys olivaceus) only found 144 DEGs out of the entire transcriptome when comparing Bold vs.…”
Section: Tablementioning
confidence: 99%